(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Concerning the importance of collective partnership, to encourage a Safe and Balanced Way of Life, PKH Facilitators in Bone District, South Sulawesi, carry out the Clean Friday Campaign initiative as a collective partnership in enforcing a sanitation or cleaning program for the village by including all KPM PKH. This paper explains what the Clean Friday Campaign is, how PKH facilitators inspire KPM PKH The study site was situated in the Bone Regency, South Sulawesi Province of the Cina District. Interviews and findings, and documentation were carried out as data collection procedures, which were then analyzed by Miles and Huberman using research theory. The study’s findings show that every Friday morning, the Clean Friday Campaign is carried out every week towards public facilities guided by the collaboration of PKH Facilitators with village and sub-district governments to increase the self-awareness of KPM in ensuring a safe atmosphere for a safe and stable existence.